The Reality of Agriculture in Nahia of Souran and The Prospects of Its Development (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to study and analyze the agricultural activity in terms of cultivation, spread and importance in the nahia of Souran to give us a clear and real picture of the agricultural process and agricultural activity in the area. The methodology of the study depends on the descriptive-analytical approach in analyzing the data that provided by the Central Bureau of Statistics and the agricultural units , to get the intended results for the investment of agriculture. The quantitative - statistical method was used for processing the statistical data and organizing them in statistical tables, in addition to the use of Arc Map 9.3 to produce local maps for the province of Hama. The study had been divided to three dialogists. The one is studying the importance, kinds and types of investment of agriculture. The second axis focused on agricultural production in Souran. The third axis dealt with the agricultural problems and the prospects of their future development. The study concluded with a group of the results, the most important was the nahia of Souran was excellent agricultural area. The Geographical location played a distinct role in agriculture. There are many problems and constraints that limit the development of the agricultural sector in Souran, followed by a set of proposals to develop the reality of agricultural activity in the study area, to get maximize use from the geographical location of the study area to serve the agricultural sector. working on the limit the impact of negative natural factors on the reality of agricultural activity in the region, reducing the problems that hinder agricultural development. The need of stimulate the agricultural investment in the research area to provide benefit the population of the region. To apply the results of agricultural research in the study area in order to get more benefits from the results of such researchs.